Effects of supplementation of grass hay with non-conventional agro-industrial by-products on rumen fermentation characteristics and microbial nitrogen supply in rams - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N.; Nsahlai, I.V. (Elsevier, 2003)
Effect of supplementation with non-conventional agro-industrial by-products on rumen fermentation pattern and microbial nitrogen supply was studied in sheep fed grass hay for 9 days. Diets consisted of hay alone (control); hay supplemented with tela atella (traditional brewery residue); katikala atella (liquor residue); lentil hull; rough pea hull and field pea hull. Thirty indigenous rams weighing 22.6±0.97 kg, were stratified into weight groups and randomly assigned to dietary treatments independently. Supplementation reduced (P<0.05) rumen pH, but improved (P<0.001) rumen ammonia, total VFA, microbial nitrogen supply (P<0.01) and microbial efficiency (P<0.05). Supplement types did not affect (P>0.05) rumen fermentation and microbial nitrogen supply, but showed difference (P<0.001) for propionate and butyrate concentrations. Type of atella supplements showed variation, whereby rumen pH was low (P<0.05), but rumen ammonia, VFA, molar proportions of acetate, propionate and butyrate were high (P<0.001) for katikala atella compared to tela atella. Lentil hull had higher (P<0.01) rumen ammonia concentration, microbial nitrogen supply and microbial efficiency than other pulse hull supplements. It was concluded that both atella and pulse hulls have potential as supplements for ruminants. More specifically lentil hull and katikala atella seemed to be superior in their diverse nutritive characteristics among the supplements studied.